Economy-Wide Estimates of the Implications of Climate Change: Sea Level Rise - Roberto Roson; Francesco Bosello; Marco Lazzarin; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2004)
The economy-wide implications of sea level rise in 2050 are estimated using a static computable general equilibrium model. Overall, general equilibrium effects increase the costs of sea level rise, but not necessarily in every sector or region. In the absence of coastal protection, economies that rely most on agriculture are hit hardest. Although energy is substituted for land, overall energy consumption falls with the shrinking economy, hurting energy exporters. With full coastal protection, GDP increases, particularly in regions that do a lot of dike building, but utility falls, least in regions that build a lot of dikes and export energy. Energy prices rise and energy consumption falls. The costs of full protection exceed the costs of losing land.
Keywords: C68; D58; Q25; 330; Impacts of climate change; Sea level rise; Computable general equilibrium; Klimawandel; Überschwemmung; Soziale Kosten; Allgemeines Gleichgewicht; Welt; Wirkungsanalyse